(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
The study demonstrates the educational program of the Italian Minister of Education, Giovanni Gentile. The “Reform of Gentile” was enacted in fascist Italy in 1923. The Reform was complex and “fluid politically”: autoritarianism was characteristic feature simultaneously with liberal methods. The fascist leader, Mussolini supported the ideas of Gentile, but when in 1924 he leaved his office, they were not the basis of the education in Italy. The Reform had many controversial details.